Data from: Olfactory cues of large carnivores modify red deer behavior and browsing intensity ... - Van Beeck Calkoen, Suzanne; Kreikenbohm, Rebekka; Kuijper, Dries; Heurich, Marco (Dryad, 2021)
This study examined the effect of perceived predation risk imposed by lynx (Lynx lynx) and wolf (Canis lupus) on red deer (Cervus elaphus) foraging behavior under experimental conditions. We hypothesized that in response to large carnivore scent red deer would increase their vigilance, while reducing the frequency and duration of visits to foraging sites. Consequently, browsing intensity on tree saplings was expected to decrease, while a higher proportion of more preferred species was expected to be browsed to compensate for higher foraging costs. We expected stronger responses towards the ambush predator lynx, compared to the cursorial predator wolf. These hypotheses were tested in a cafeteria experiment conducted within three red deer enclosures, each containing four experimental plots with olfactory cues of wolf, lynx, cow, and water as control. On each plot, a camera trap was placed and browsing intensity was measured for one consecutive week, repeated three times. Red deer reduced their visitation ... : See "Methods" and "Statistical analyses" section article ...